A strategy for risk control of marine pollution from land-based sources: establishment of Multilateral Guarantee Mechanism - Pan, Xiaolin (Frontiers in Marine Science, 2025)
Marine pollution from land-based sources (MPLBS) is currently one of the main sources of global marine pollution. The international community is facing a dilemma on regulating MPLBS: the lack of international rules makes it difficult to resort to international judicial institutes, while domestic laws have no extraterritorial jurisdiction. Along with developing and improving the international legal regulatory system, the Multilateral Guarantee Mechanism (MGM) can be established for MPLBS combat. With its unique advantages, the MGM is beneficial for controlling MPLBS risk, supervising pollutant sources, and providing effective compensation for damages. Section 1 of this article starts with a brief introduction to the definition and features of MPLBS. With its wide scope not limited to the coastal waters, MPLBS could lead to serious harmful consequences to the marine environment, and it is difficult to trace the real sources of the pollutants. Section 2 analyzes the legal challenges faced by MPLBS combat and points out the necessity of constructing the risk control mechanism for MPLBS. The absence of a specific worldwide international treaty becomes one of the deficiencies for international legal norms regarding MPLBS control, while comparatively integrated domestic legal frameworks on MPLBS control only take effect within territories and jurisdictional waters of states. The establishment of a risk prevention and control mechanism, which also aims to provide effective injury compensation, is more practical and appropriate. Section 3 discusses the necessity, feasibility, and advantages of the MGM for MPLBS risk control. The dilemma of MPLBS control constitutes the necessity of establishing MGM, and the commonalities between international investment risk control and MPLBS risk control show the feasibility of MGM establishment. The advantages of MGM also help to balance national interests and collective environmental protection. Section 4 explores how the MGM functions for MPLBS risk control by referring to a series of core contents, including fundamental convention, guarantee agency, types of risks, payment and subrogation, dispute settlement, and so forth. Section 5 illustrates the implementation of the MGM under two hypothetical scenarios: plastic pollution in the Philippines and Japanese radioactive wastewater pollution. Restrictions of the MGM and corresponding solutions are also discussed. Section 6 concludes the main arguments and makes an expectation on the MGM.